Patterns of abundance, population size, structure and microhabitat usage of Paracentrotus lividus (Echinodermata: Echinoidea) in SW Portugal and NW Italy - Jacinto, D. (2014)
In coastal habitats, wave exposure influences several aspects of the life history of marine organisms. Here, we assess how hydrodynamic conditions can gener- ate variation in density, size structure and microhabitat usage of Paracentrotus lividus and whether these effects are consistent between regions that are markedly different for oceanic climate, such as the coasts of SW Portugal and NW Italy. The abundance of P. lividus was *4 times higher in SW Portugal than in NW Italy, but within each region, there was no effect of wave exposure. In SW Portugal, higher urchin abundances were found at shal- lower depths, while no effect of depth on urchin abundance emerged in NW Italy. Most of the variation in urchin abundance occurred at small spatial scales (metres), and our results suggest that habitat complexity, that is, the presence of cracks and crevices, is an important determi- nant of patterns of distribution of this species. The popu- lation in NW Italy was characterized by a unimodal size distribution, with a higher proportion of medium-sized individuals. In contrast, in SW Portugal, smaller individ- uals represented a large proportion of the populations. Size structure varied between exposed and sheltered habitats in SW Portugal, suggesting that the proportion of individuals from different size cohorts may vary along wave-exposure gradients as a result of direct or indirect effects of hydrodynamic forces. In SW Portugal, most urchins occurred in burrows, while in NW Italy, urchins were mainly observed in crevices. These results suggest that creating/occupying burrows might be an adaptive behav- iour that allows sea urchins to better withstand stressful hydrodynamic conditions and, therefore, are more common on exposed Atlantic coasts. Overall, our study suggests that the effects of hydrodynamic forces on sea urchin popula- tions are context dependent and vary according to back- ground oceanic climate.